Green tribology for the sustainable engineering of the future - Kalin, Mitjan (Strojniški vestnik, 2019)
Environmental awareness and especially the legislation that requires the reduction of polluting emissions are strong driving forces toward more sustainable engineering and greener solutions in the design, use and overall life span of machinery. However, providing novel concepts that will exclude non-environmentally adapted, but over many years developed and optimized solutions, is not an easy task. It clearly requires time if the same level of technical performance is to be maintained. Green tribology is one of the fields that has been closely involved in these actives in the past two decades. The research and use of tribology science and technology toward green and sustainable engineering include natural material usage, lower energy consumption, reducing natural oil resources, reducing pollution and emissions, fewer maintenance requirements and thus reduced machinery-investment cycles. This report is not an attempt to cover all the existing concepts, attempts or literature available in the field, but mainly those efforts that our group has been working on over the past 20 years, which mainly includes novel green-lubrication concepts that come from exploring and exploiting surface engineering through the use of diamond-like-carbon (DLC) coatings.
Keywords: biodegradable oils; biološko razgradljiva olja; boundary slip; DLC coatings; DLC prevleke; green lubrication; ionic liquids; ionske tekočine; low SAPS oils; mejni zdrs; nanodelci; nanoparticles; olja z nizkim deležem SAPS aditivov; vodno mazanje; water lubrication; zeleno mazanje